Evaluation of Microorganisms in Cervical Smears: A Single Institutional Experience - Alwahaibi, Nasar; Alrubkhi, Mai Mohammed; Rani Bai, Usha (Asian Pacific Journal of Cancer Biology, 2019)
Human papilloma virus (HPV) and herpes simplex virus (HSV) are common microorganisms investigated in the diagnosis of cervical abnormalities, however other microorganisms have received less attention. This study aimed to identify different microorganisms present in cervical smears as well as to determine the association between those microorganisms and cervical abnormalities. A retrospective study was conducted from January 2008 to December 2012, evaluating the presence of microorganisms in cervical smears. The association between the microorganisms and cervical abnormalities was studied by using the odds ratio and relative risk tests. A total of 7112 cervical smears were analyzed. The mean age of the patients was 39.13 years (range 17 – 80). Bacteria were the most common microorganism but it showed no association with cervical abnormalities. HPV, HSV and Trichomonas vaginalis are the least common but showed a positive association with a relative risk of 16.59, 7.23 and 1.15 respectively. Bacteria and fungi are the most common microorganisms present in cervical smears but they are not associated with cervical abnormalities whereas HPV and HSV are less common but they are associated with cervical abnormalities.